Bridging Ancient Wisdom and Digital Innovation in Modern Pharmacognosy - KK, Mueen Ahmed (Pharmacognosy Reviews)
The current issue of Pharmacognosy Reviews (Volume 19, Issue 38, July-December 2025) presents a remarkable convergence of traditional botanical knowledge and cutting-edge artificial intelligence applications in drug discovery. This collection of twelve comprehensive reviews and research articles illuminates the evolving landscape of pharmacognosy, where millennia-old plant-based therapeutics meet 21st-century computational methodologies. The editorial board has curated a diverse yet thematically coherent compilation that addresses critical gaps in natural product research while charting new territories for therapeutic innovation.